Sistem Pendukung Keputusan Menentukan Kualitas Kinerja Dosen Selama Kuliah Online Menggunakan Promethee II - Ita Arfyanti; Rajiansyah Rajiansyah (STMIK Budi Darma, 2021)
Lecturer performance is a quality of self that is given entirely to fulfill the responsibilities of a teacher in a tertiary institution, towards students or students in fulfilling student rights, the importance of knowing that the quality of lecturer performance will affect the level of student learning desire, especially during the Covid-19 pandemic, lecturer performance considered capable of improving the learning process that must be done online, online learning often results in a lack of communication between lecturers and students. Accumulation was carried out on a decision support system to see each of the lecturers 'performance qualities at STMIK Widya Cipta Dharma during online lectures using the Promethee II method, the results displayed were the highest score of